2021
DOI: 10.3389/fpsyg.2021.666079
|View full text |Cite
|
Sign up to set email alerts
|

Social Innovation Toward a Meaningful Everyday Life for Nursing Home Residents: An Ethnographic Study

Abstract: Background: The literature shows that innovation, which includes culture change, may be important to create a meaningful everyday life for nursing home residents. However, there is a gap in how social innovation practices may contribute to this. The theoretical discourse for the study is person-centered care.Aim: The main aim was to explore phenomena within social innovation that can contribute to improving nursing home residents’ everyday lives.Design and Method: This study uses an ethnographic design with ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Regarding the first aspect, a recent qualitative study indicated that an open NH contributed to meaningful everyday life for the residents. The NHs were open institutions, meaning that they extended into the community and invited the community into the NHs to participate in activities (Slettebø et al, 2021). When not being attended to or treated with indifference, NH residents reported feelings of frustration and suffering (Bakas et al, 2012; Haugan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the first aspect, a recent qualitative study indicated that an open NH contributed to meaningful everyday life for the residents. The NHs were open institutions, meaning that they extended into the community and invited the community into the NHs to participate in activities (Slettebø et al, 2021). When not being attended to or treated with indifference, NH residents reported feelings of frustration and suffering (Bakas et al, 2012; Haugan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Spiritual well-being is a crucial factor in maintaining positive mental health for older adults. Social innovation has been shown to contribute to enhancing the meaning and purpose of daily life for nursing home residents [ 102 ]. In a recent study, the process of spiritual care was found to involve identifying the spiritual needs and resources of older adults in healthcare, understanding their specific requirements, developing a personalized spiritual care treatment plan, and engaging relevant healthcare and spiritual care professionals to facilitate personal connections with meaning-making agents [ 103 ].…”
Section: Maintainable Positive Mental Health In Late Lifementioning
confidence: 99%
“…Although physical care used to be the most prominent focus, recently, there has been a shift toward a holistic view of the person and person-centered care, which requires seeing the whole person and their physical, psychological, spiritual, and social dimensions. There has been a change from more passive care to active care, with meaningful activities highlighted as important in long-term care (3). There have been multiple high-quality trials and systematic reviews that provide evidence for good practice in long-term residential institutions for older adults, referred to in many countries as nursing homes, also known as long-term CH, homes for the aged, rest homes, and residential aged care facilities (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%